Wire Arc Additive Manufacturing of Stainless Steels: A Review - Wanwan Jin; Chaoqun Zhang; Shuoya Jin; Yingtao Tian; Daniel Wellmann; Wen Liu (Applied Sciences, 2020)
Wire arc additive manufacturing (WAAM) has been considered as a promising technology for the production of large metallic structures with high deposition rates and low cost. Stainless steels are widely applied due to good mechanical properties and excellent corrosion resistance. This paper reviews the current status of stainless steel WAAM, covering the microstructure, mechanical properties, and defects related to different stainless steels and process parameters. Residual stress and distortion of the WAAM manufactured components are discussed. Specific WAAM techniques, material compositions, process parameters, shielding gas composition, post heat treatments, microstructure, and defects can significantly influence the mechanical properties of WAAM stainless steels. To achieve high quality WAAM stainless steel parts, there is still a strong need to further study the underlying physical metallurgy mechanisms of the WAAM process and post heat treatments to optimize the WAAM and heat treatment parameters and thus control the microstructure. WAAM samples often show considerable anisotropy both in microstructure and mechanical properties. The new in-situ rolling + WAAM process is very effective in reducing the anisotropy, which also can reduce the residual stress and distortion. For future industrial applications, fatigue properties, and corrosion behaviors of WAAMed stainless steels need to be deeply studied in the future. Additionally, further efforts should be made to improve the WAAM process to achieve faster deposition rates and better-quality control.